Autism Spectrum Disorders and Implications for Teachers - Echaniz, Crystal; Cronin, Kathleen A. (Journal of the American Academy of Special Education Professionals, 2014)
This paper reviews characteristics of autism spectrum disorders (ASD), possible causes of ASD, current demographic information, the effects on the individual with ASD and the family, as well as diversity and multicultural issues related to autism. Additionally, the paper provides pertinent information about students with ASD for both general education and special education teachers including a review of special education laws, pedagogical strategies, the individual education plan (IEP), the use of behavior plans, accommodations and modifications appropriate for students on the autism spectrum, assistive technology, and professional development.